MENGHINDARKAN REMAJA DARI PENYALAHGUNAAN NARKOBA MELALUI INTERVENSI IDENTITAS - Nanik Yuliati (Psympathic : Jurnal Ilmiah Psikologi, 2011)
This paper intended to give a conceptual framework in order to prevent adolescent from drug abuse by using a developmental approach. Search for identity is one aspect of psychosocial development which very crucial in periods of adolescence and most developmentalist which agree that healthy or unhealthy personality developmental be attributable to the process of search for identity. Most developmentalist have a belief that adolescents achieve a sense of identity tend to demonstrate a healthy and constructive behavior, while failing achieve becoming vulnerable to  various forms of psychosocial disturbance, one of which drug abuse. Therefor, to prevent teenagers from drug abuse we can do with helping them to achieve a sense of identity.